Exploring the Construct of Relational Values: An Empirical Approach - Kleespies, Matthias Winfried; Dierkes, Paul Wilhelm (Frontiers in Psychology, 2020)
In recent environmental research, relational values (RV) have emerged as a new group of values to explain environmental behavior. Although this new concept is attracting attention, empirical studies on the subject are still rare. On this basis, we have conducted three studies to analyze an existing measurement tool for RV and compared the construct with the concept of connection to nature. In study 1 we confirmed convergent and discriminant validity of the RV scale by comparing it with the 2-MEV model using a sample of n = 350 university students. Additionally, study 1 verified reliability using test-retest-reliability on three different groups of students (n1 = 53; n2 = 37; n3 = 48). In study 2 principal component analyses were performed to examine the structure of RV and to compare it to the concept of connection to nature reusing the sample 350 university students from study 1. The results show that RV and connection to nature are not fundamentally distinct constructs, but overlap. However, if the structure of the RV measurement is forced to a single factor, no perfect fit is found, making a multidimensional solution more likely. A third study was conducted to review the results from study 2 using confirmatory factor analysis on a new sample of 878 university and high school students. Study 3 confirmed RV as a multidimensional construct with three factors: care, community and connection. It also proved the overlap of the connection to nature and RV concepts to some extent.